IT Infrastructure Library Framework Approach to the Measurement of e-Government Maturity - Batmetan, Johan Reimon; Nur, Muhammad; Turang, Omega S.M.; Sumampouw, Merry M. (JR Education, 2022)
This research was conducted to improve E-Government services on the Manado smart city application to the smart city and determine the level of readiness and feasibility of the Manado smart city application using the ITIL method in the service design domain and transmission service using the Information Technology Infrastructure Library (ITIL) framework. The purpose of this study is to measure the level of marturity of the smart city and help the Manado city government in knowing the maturity level of Manado City towards a smart city. The research method used is the method of measuring the level of marturity using the ITIL framework. The results of this study show that this smart city application can be used at any time, especially at the Manado command center which can monitor the activities of each vehicle and various problems that cause congestion and can be seen from human resources for the usefulness of this application, there are still many who do not know and feel results, impact and benefits of this smart application. Many residents or residents of Manado do not use this smart city application technology.